THE STUDY OF THE ART OF MUSIC IN THE DEVELOPMENT OF PERSONALITY MATURATION - Xoliqnazarov Xurshid Holmatjon ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the Achaemenid nature of musical art in the development of personality maturation.